Research on a Small Modular Reactor Fault Diagnosis System Based on the Attention Mechanism - Sicong Wan; Jichong Lei (Energies, 2025)
Small modular reactors are progressing towards greater levels of automation and intelligence, with intelligent control emerging as a pivotal trend in SMR development. When contrasted with traditional commercial nuclear power plants, SMR display substantial disparities in design parameters and the designs of safety auxiliary systems. As a result, fault diagnosis systems tailored for commercial nuclear power plants are ill-equipped for SMRs. This study utilizes the PCTRAN-SMR V1.0 software to develop an intelligent fault diagnosis system for the SMART small modular reactor based on an attention mechanism. By comparing different network models, it is demonstrated that the CNN–LSTM–Attention model with an attention mechanism significantly outperforms CNN, LSTM, and CNN–LSTM models, achieving up to a 7% improvement in prediction accuracy. These results clearly indicate that incorporating an attention mechanism can effectively enhance the performance of deep learning models in nuclear power plant fault diagnosis.